The study of pulmonary function tests in patients with hypothyroidism - H., Sivaranjani; R., Chaitra K. (International Journal of Advances in Medicine, 2019)
Background: Hypothyroidism is a common disease with a prevalence rate of 11% in India. It affects all organ systems in the body. Patients with hypothyroidism frequently have symptoms of fatigue and exercise intolerance. These symptoms could arise from a reduced pulmonary reserve, cardiac reserve or decreased muscle strength or increased muscle fatigue. This study aims to study the pulmonary function test in patients with hypothyroidism. Methods: This is a cross sectional study conducted on 100 patients divided into 2 groups (a) newly detected hypothyroids (b) normal control group. Cases were matched with controls in having similar environment exposure and age group. All patients had routine symptom and clinical assessment. Laboratory investigations such as complete blood picture, pulmonary function test, chest x ray and thyroid function test were done. Data was entered and analysed. Results: In this study conducted on 100 patients, case group had symptoms of easy fatiguability (36%), breathlessness (20%), menstrual abnormality (20%), weight gain (7%) and generalised body aches (5%). Mean FEV1 levels between cases and controls were 1.34 and 1.72 (p value 0.00), mean FVC were 1.88 and 2.09 (p value 0.114), FEV1/FVC ratio of 70.56, 81.98 respectively (p value 0.00). The distribution of PFT pattern was 32% obstructive, 28% mixed pattern and 22% restrictive pattern. Conclusions: This study shows that hypothyroidism causes significant decrease in FEV1 and FEV1/FVC ratio, thereby suggesting obstructive patterns of lung involvement .Therefore PFT can be used routinely as a screening test for all hypothyroid patients to detect early respiratory dysfunction and thereby optimise treatment especially in obese patients and patients with pre-existing lung disease as hypothyroidism adds to their respiratory dysfunction.